Meningkatkan Kemampuan Mengenal Warna Melalui Permainan Finger Painting pada Anak Gangguan Spektrum Autisme (GSA) (Single Subject Research Kelas I di SLB YPPLB Padang) - Lestari, Ocha Dwi; Rahmahtrisilvia, Rahmahtrisilvia; Iswari, Mega; Arnez, Gaby; Handayani, Endang Sri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the color recognition ability for students with Autism Spectrum Disorder (ASD) in the first grade at SLB YPPLB Padang using finger painting games. This research employs a quantitative research type with an experimental approach in the form of Single Subject Research (SSR) with an A-B design. The data analysis technique in this study is visual data analysis by presenting data graphs. The results of the data analysis obtained at the baseline condition (A1) show a horizontal trend for the subjects with a level of horizontal change (+0). The stability trend at the initial condition is stable with a percentage of 100% occurring three times in meetings: 25%, 25%, 25%. At the baseline condition (A), it can be seen that the direction of data change is stable with no changes before the intervention was carried out. Observations during the intervention condition (B) showed a level of change (+56.25), indicating an improvement in color recognition ability with percentages from 8 meetings being 43.75%, 68.75%, 75%, 87.5%, 87.5%, 100%, 100%, and 100%. The data direction shows a very significant increase and an overlap percentage of 0%. This illustrates a clearer development in the students' abilities, suggesting that the intervention provided has a positive impact on the variable.